Reduction of Climate Risk as a Key to Business Performance – Framework for Sustainable Corporate Treasury Management (CTM) - Michalski, Grzegorz (Ograniczenie ryzyka pogodowego kluczem do wyników biznesowych – ramy zrównoważonego zarządzania finansami przedsiębiorstw (CTM), 2025)
Aim: The article aims to examine the impact of climate instability risk on Corporate Treasury Manage-ment (CTM) and demonstrate that sustainable strategies can effectively mitigate this risk while enhancing corporate financial performance. Methodology: A theoretical and empirical approach is employed, including econometric modelling, case study analysis, and literature review, with a focus on the use of financial instruments – particularly climate derivatives – within CTM. Results: Effective management of climate risk through sustainable policies and financial instruments raises treasury levels and strengthens corporate competitiveness by reducing unexpected losses and the costs of maintaining high liquidity reserves. Implications and recommendations: The study recommends incorporating environmentally conscious strategies into CTM and implementing fiscal incentives and regulatory frameworks to support climate risk hedging tools. Further research should explore sector-specific applications of sustainable CTM, especially in climate-sensitive industries. Originality/value: The article offers a novel integration of sustainability and treasury optimisation, showing that environmental responsibility can directly support and enhance core financial goals within CTM frameworks.
Econometrics = Ekonometria, 2025, Vol. 29, No. 1, s. 15-39
Keywords: climate risk; sustainable treasury management; effectiveness of the entity; Corporate Treasury Management; ryzyko pogodowe; zrównoważone zarządzanie finansami; wyniki finansowe przedsiębiorstw